Watermelon Production in Dry Land with Liquid Biofertilizer and Different Compound NPK - Neni Marlina; Khodijah Khodijah; Ida Aryani; Dita Purnama Sari (Journal of Global Sustainable Agriculture, 2021)
An area of 12.90 million ha of dry land has not been used optimally for agriculture, opportunity available to plant watermelons with proper cultivation techniques, including the use of biological and inorganic fertilizers. Biofertilizers can help provide NPK nutrients for watermelon plants. The purpose of this study was to determine the appropriate dosage of biological fertilizers and compound NPK for increasing watermelon yields. The research was conducted at AKN Sakojo No.21 Kel. Kedondong Raya Kec. Banyuasin III Pangkalan Banyuasin City Hall, South Sumatra from July to October 2020. This study used a factorial randomized block design (RAK). Factorial 1 is the dose of liquid biological fertilizer, namely: 10 mL/L, 20 mL/L, and 30 mL/L. Factorial II is Compound NPK, namely: 600 kg/ha, 900 kg/ha, and 1200 kg/ha. The highest production of 22.32 kg/plot (38 tons/ha) was achieved at a dose of 30 mL/L of liquid biological fertilizer and 1200 kg/ha of compound NPK fertilizer.